Trauma-related retrobulbar hematoma: predictive risk factors and clinical outcome in 52 cases - Ákos Bicsák; Hüseyin Şahin; Lena Brandt; Stefan Hassfeld; Lars Bonitz (European Journal of Trauma and Emergency Surgery, 2026)
Abstract Purpose Retrobulbar hematoma (RBH) is a vision-threatening emergency. This large-scale study integrates clinical data and 3D analysis to identify prognostic factors, refine diagnosis, and support guideline-based emergency management. Methods This study standardizes terminology, applies AO fracture classification, and uses CT-based 3D segmentation to analyze anatomical patterns, treatment protocols, providing evidence-based guidance for diagnosis, surgical management, and postoperative care. Results The Dortmund Maxillofacial Trauma Registry (2018–2025) recorded 52 RBHs among 7,671 trauma patients (0.7%). RBH occurred predominantly in middle-aged males and elderly females, with overproportionate incidence of anticoagulant therapy. Most fractures clustered around the orbital floor, medial wall, zygomatic surface, often near the Frankfurt horizontal plane. RBHs were mainly extraconal; poor outcome was predicted with intraconal location, optic nerve contact, orbital floor fracture, high RBH/orbital volume ratio, and aspirin use. Surgical decompression was performed in 15 cases (28.9%); 65,4% (34 of 52) retained vision. Neural network analysis confirmed fracture site and hematoma position as key prognostic factors over demographic or comorbidity variables. Conclusion In 7,671 midface fracture cases, RBHs occurred in 0.7% ( n = 52), mainly after trauma. Falls predominated in aetiology; orbital floor and zygomatic fractures were most frequent. Blindness occurred in 3.8%. Prompt decompression remains critical; volumetric analysis offers new prognostic insight. All midface fracture or periorbital hematoma patients require urgent ophthalmologic assessment with prompt decompression when indicated. A suggested checklist to support emergency diagnostics presents findings. We recommend 48-hour observation to prevent vision loss from delayed post-traumatic ocular complications.